Efeitos do extrato aquoso de cebola (Allium cepa L.) sobre a função renal e a pressão arterial em ratos Wistar - Campos, K. E. [UNESP]; Balbi, A. P C; Alves, M. J Q F [UNESP] (My University, 2005)
The vegetal species, Allium cepa, known as onion, is widely used in the folk medicine as diuretic, besides it has been used on the bronchitis, cough, cardiovascular diseases and hypertension treatment. In this study we evaluate the onion aqueous extract (AE) effect on water flow and electrolytes in anesthetized Wistar rats, besides we also evaluate arterial pressure alterations. Two groups were studied: Group 1 (control) - oral tratment with 1.0 mL of distilled water, and Group 2 (experimental) - oral treatment with 1.0 mL of AE 20%. The rats were anesthetized and we canulate the trachea, left carotide artery (for arterial pressure measurement and blood collecting), jugular vein (to execute inulin perfusion - to register glomerular filtration), and urinary bladder (to collect urine). The Group 1 results had shown that the animals had not presented significant alterations (p>0.05) in the analyzed parameters. The animals of Group 2 had a significant reduction (p<0.05) in the arterial pressure (22.0%). However, there were not significant alterations in renal parameters (p>0.05). These results show that the treatment with the AE lead a hypotensor effect in anesthetized Wistar rats, but not followed by renal parameters alterations.
Effects of onion aqueous extract under the renal function and the arterial pressure in Wistar rats
Keywords: Arterial hypertension; Onion; Rats wistar; Renal function; electrolyte; inulin; onion extract; anesthesia; animal experiment; arterial pressure; bronchitis; cannulation; cardiovascular disease; carotid artery; controlled study; coughing; diuresis; drug effect; electrolyte balance; glomerulus filtration; hypertension; hypotension; jugular vein; kidney function; nonhuman; rat; trachea; traditional medicine; urine volume; water flow; Allium cepa; Animalia; Rattus norvegicus